Efektivitas Administrasi PKWT dalam Pengelolaan Data Karyawan di PT Wijaya Kusumo Joyo Mulyo - Septiana Devita Nurfadela; Mochammad Isa Anshori (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the effectiveness of the administration of Fixed Term Employment Agreements (PKWT) in managing employee data at PT Wijaya Kusumo Joyo Mulyo. Well-organized PKWT administration has a strategic role in ensuring compliance with employment regulations and efficient human resource management. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the administration of PKWT in the company has been running quite effectively, as indicated by the existence of a structured contract recording system, compliance with the duration of PKWT according to government regulations, and systematic document archiving. However, several obstacles were found such as delays in contract extensions and the lack of integration of PKWT data with the digital HR management system. These findings indicate that although PKWT administration has met most of the effectiveness indicators, improvements are still needed in the aspect of information technology integration to support more efficient and accurate employee data management.